Efficacy and safety of anlotinib for triple-negative breast cancer with brain metastases - Liu, Zeyu; Li, Ming; Zhao, Ziyi; Liu, Aina; Sun, Ping (Frontiers in Oncology, 2024)
BackgroundThe anti-angiogenic agent anlotinib offers a new treatment option for triple-negative breast cancer (TNBC) patients with brain metastases. This study aimed to evaluate the efficacy and safety of anlotinib in the treatment of TNBC patients with brain metastases.MethodsBetween October 2019 and April 2024, 29 TNBC patients with brain metastases who had failed prior therapy and were treated with anlotinib were retrospectively analyzed. The primary endpoint was central nervous system (CNS) progression-free survival (PFS), and secondary endpoints included overall survival (OS), intracranial disease control rate (iDCR), intracranial objective response rate (iORR), and safety.ResultsThe median CNS PFS of 29 patients was 7.2 months (95% confidence interval [CI], 3.5-10.9 months), and the median OS was 10.2 months (95% CI, 5.6-14.8 months). The iORR and iDCR were 31.0% and 86.2%, respectively. Five patients (17.2%) experienced grade 3-4 adverse events (AEs), with bone marrow suppression (2/29, 6.9%) being the most common. Most AEs were clinically manageable, and no treatment-related death was observed.ConclusionAnlotinib demonstrated encouraging efficacy and manageable toxicity in the treatment of TNBC patients with brain metastases who had failed standard treatment.